(untitled) - Ter Haar, Gerrit Matthys

Selective laser melting-produced Ti6Al4V: Influence of annealing strategies on crystallographic microstructure and tensile behaviour (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.